Penerapan Permainan Tradisional untuk Meningkatkan Motivasi Belajar PJOK di SDN Betet 3 Kediri. - Muhammad Annas Nur Arifin; Muhammad Akbar Husein Allsabah; Moh. Aan Zainul Arifin (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to determine the effect of traditional games on student learning motivation in physical education classes for fourth graders at SDN Betet 3 Elementary School in Kediri City. This study is a classroom action research (CAR) conducted in two cycles. The research subjects were 26 students (15 boys and 11 girls). The data collection instrument used was a learning motivation questionnaire. The results showed an increase in student learning motivation. In the initial observation, motivation only reached 45.76%. After the implementation of the traditional game of kasti in cycle I, motivation increased to 55.38%. In cycle II, with the implementation of the engklek game, motivation increased significantly to 86.54%. Thus, it can be concluded that the implementation of traditional games is effective in increasing student motivation in PJOK learning.